[RETRACTED] Determining Factors of Eco-Innovation Adoption: An Empirical Study of Micro and Small Enterprises in Johannesburg, South Africa: Retraction Notice: The article by K. Sichoongwe titled "Determining Factors of Eco-Innovation Adoption: An Empirical Study of Micro and Small Enterprises in Johannesburg, South Africa," published in The Winners (2023; 24(1). https://doi.org/10.21512/tw.v24i1.10035), has been retracted due to redundant publication. A substantially similar version of the arti - Sichoongwe, Kiru (Journal The Winners, 2023)
Eco-Innovation (EI) is a typical innovation that is beneficial to the environment. It is seen as a necessary step that positively contribute to the worldwide fight against carbon emissions. It is a crucial component for achieving sustainable development and improving environmental and economic performance. The research investigated what drives micro and small enterprises (MSEs) to adopt environmental innovation technologies in Johannesburg, South Africa. An econometric model was used to examine a total of 1,021 MSEs. The probit findings show that environmental tax, government subsidies, and research and development (R&D) activities, have a positive influence on EI adoption. Also, adoption of EI is dependent on the successful application of non-eco-innovations (e.g., innovation on new products, innovation on improved products, and innovation on improved services) by enterprises. The resarch concludes with policy implications.